Tsetse and trypanosomes relationship in Southwestern part of Burkina Faso - SALOU, Ernest Wendemanegde; KABORE, Jacques; BOMA, Soudah; AGBOHO, Prudenciène; YONI1, Wilfrid; BENGALY, Zakaria (Sciences de la Santé, 2024)
African Animal Trypanosomosis (AAT), transmitted by tsetse flies, are one of the main constraints for the development of livestock farming in Burkina Faso. The objective of this study was to understand the impact of the level of degradation of tsetse habitat on the epidemiology of AAT. Entomological and parasitological surveys were carried out in two different landscape areas: conserved (Folonzo) and fragmented (Moussodougou) in southwestern part of Burkina Faso. The results revealed that the diversity, abundance and infection rate of tsetse flies were related to the conservation status of the habitat. In Folonzo, four species of tsetse were present (84.76% (2870/3386)) versus a single species (15.24%) in Moussodougou. The tsetse infection rate was also higher in Folonzo (21% (133/633)) than in Moussodougou (7.8% (23/294)). In addition, in Folonzo, the tsetse flies were infected with all 3 species of trypanosomes. However, in Moussodougou, G. p. gambiensis (the only species present) was infected primarily with T. congolense (68.44% (13/19)). We suggest that the current fragmentation of tsetse habitats does not reduce the risk of trypanosomiasis, but leads to selection and maintaining the best trypanosome and tsetse (G. p. gambiensis / T. congolense) pair that may affect the epidemiology of AAT.